2008
DOI: 10.1086/526514
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Only Some Galaxy Clusters Have Cool Cores?

Abstract: Flux-limited X-ray samples indicate that about half of rich galaxy clusters have cool cores. Why do only some clusters have cool cores while others do not? In this paper, cosmological N-body + Eulerian hydrodynamic simulations, including radiative cooling and heating, are used to address this question as we examine the formation and evolution of cool core (CC) and non-cool core (NCC) clusters. These adaptive mesh refinement simulations produce both CC and NCC clusters in the same volume. They have a peak resol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
186
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(219 citation statements)
references
References 63 publications
31
186
2
Order By: Relevance
“…to the range spanned by the Planck clusters) increases its undisturbed fraction to 26 per cent, reducing the evidence of a trend with redshift, while not significantly changing the picture for the peaky fraction. Both the absolute value of the SZ peaky fraction (14 per cent overall) and its constant behavior with redshift are consistent with the predictions of hydrodynamical simulations (Burns et al 2008, Planelles & Quilis 2009). However, the same simulations predict a decreasing cool-core fraction with cluster mass, which contradicts the increasing fraction of peaky clusters with temperature observed for the SZ sample.…”
Section: Trends With Redshift Temperature and Parent Samplesupporting
confidence: 84%
See 1 more Smart Citation
“…to the range spanned by the Planck clusters) increases its undisturbed fraction to 26 per cent, reducing the evidence of a trend with redshift, while not significantly changing the picture for the peaky fraction. Both the absolute value of the SZ peaky fraction (14 per cent overall) and its constant behavior with redshift are consistent with the predictions of hydrodynamical simulations (Burns et al 2008, Planelles & Quilis 2009). However, the same simulations predict a decreasing cool-core fraction with cluster mass, which contradicts the increasing fraction of peaky clusters with temperature observed for the SZ sample.…”
Section: Trends With Redshift Temperature and Parent Samplesupporting
confidence: 84%
“…There are several known examples of cool cores being destroyed by ram pressure stripping as they oscillate (slosh) about the bottom of the cluster potential following a merger (Markevitch et al 2000, Mazzotta et al 2001, Million et al 2010, Ehlert et al 2011, Ichinohe et al 2014, a process also observed in hydrodynamic simulations (e.g. Burns et al 2008, ZuHone et al 2011. Hence a possible explanation is that mergers with the necessary mass ratio and impact parameter to destroy a hosted cool core via sloshing are relatively less common for the most massive clusters, despite these clusters having a larger merger rate overall; this would be qualitatively consistent with the larger undisturbed fraction we observe for the most massive clusters.…”
Section: Trends With Redshift Temperature and Parent Samplementioning
confidence: 99%
“…The NCC systems follow the observational relation reasonably well. The fossil cluster and the CC systems however show a very large central gas fraction, in many cases even above the universal gas fraction (similar to the results of Burns et al 2008). This result is clearly in tension with the results of Mantz et al (2014), and reflects the high electron densities and very low central entropies we have seen for the CC systems above.…”
Section: Gas Depletion Profilessupporting
confidence: 75%
“…However, once including the continuing mass accretion the cluster growth rate since z 1 is much faster. The simulations of Burns et al (2008) predict average mass growth rates of 5−10% per Gyr at late times and 30−50% per Gyr during active mass assembly periods around z ∼ 1. As a benchmark, the time evolution of the largest local ∼10 15 M halo in the Millennium-II simulation (Boylan-Kolchin et al 2009) exhibits a total mass increase since z ∼ 1 by more than a factor of 5.…”
Section: Appearance At Z =mentioning
confidence: 98%
“…This scenario is consistent with the emerging picture from simulations on the different formation histories of NCC and CC clusters. The simulations of Burns et al (2008) showed that Non-Cool-Core clusters are characterized by an increased mass accretion rate ( > ∼ 50% per Gyr) in early epochs (z > ∼ 0.8), during which nascent cool cores are destroyed by major merger events which also set the conditions to prevent cooling at later epochs.…”
Section: Dynamical State Of Xmmu J12303+1339mentioning
confidence: 99%